Fin Whale Song Patterns Shift Over Time in the Central North Pacific - Helble, Tyler A.; Guazzo, Regina A.; Alongi, Gabriela C.; Martin, Cameron R.; Martin, Stephen W.; Henderson, E. Elizabeth (Frontiers in Marine Science, 2020)
Male fin whales sing by producing 20-Hz pulses in regular patterns of inter-note intervals. While singing, fin whales may also alternate the frequency ranges of their notes. Different song patterns have been observed in different regions of the world's oceans. New song patterns suddenly emerging in an area have been hypothesized to either be indicators of new groups of whales in the area or signs of cultural transmission between groups. Since the status of fin whales around Hawaii is unknown and visual surveys are expensive and difficult to conduct in offshore areas, passive acoustic monitoring has been proposed as a way to monitor these whales. We used passive acoustic recordings from an array of 14 hydrophones to analyze the song patterns of 115 fin whale encounters made up of 50,034 unique notes off Kauai, Hawaii from 2011--2017. Fin whale singing patterns were more complicated than previously described. Fin whales off Hawaii sang in five different patterns made of two 20-Hz note types and both singlet and doublet inter-note interval patterns. The inter-note intervals present in their songs were 28/33 s for the lower frequency doublet, 30 s for the lower frequency singlet, 17/24 s for the higher frequency doublet, 17 s for the higher frequency singlet, and 12/20 s for the doublet that alternated between both note types. Some of these song patterns were unique to these fin whales in Hawaiian waters, while others were similar to song patterns recorded from fin whales off the U.S. west coast. Individual fin whales often utilized several different song patterns which suggests that multiple song patterns are not necessarily indicators of different individuals or groups. The dominant song pattern also changed over these years. Cultural transmission may have occurred between fin whales in Hawaiian waters and off the U.S. west coast, which has resulted in similar songs being present at both locations but on lagged timescales. Alternatively, groups occupying the Hawaiian waters could shift over time resulting in different song patterns becoming dominant. This work has implications for the population structure and behavior of Hawaii fin whales.